1996
DOI: 10.1080/10406639608048351
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of Acridine, an Important Representative of a Group of Tar and Creosote Contaminents, N-Pac Compounds

Abstract: N-PAC (azaarenes) occur in the environment at levels that are 1-10% of the analogous polycyclic aromatic hydrocarbons (PAH), e.g. from the production and use of creosote and tar. In this investigation navew (Brassica campestris L.), Italian rye-grass (Loliurn multiporum L.) and barley (Hordeurn uulgare L.) were grown in two different soils containing concentrations of 0, 1 and 100 ppm acridine. The observations reveal that acridine inhibits the seed production of navew and the growth of Italian rye-grass. Inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Several studies have reported that seed germination may be insensitive to toxic chemicals in soil as seedlings derive their food from internal materials (Sverdrup et al 2003;Eom et al 2007;Chung et al 2007;Smith et al 2006). In contrast, however, Henner et al (1999) reported that volatile, water soluble, low molecular weight hydrocarbons (<3-rings) such as 1,7-PHENANTHROLINE (wet biomass) TIME (d) In this current study, however, the observed inhibitory effect of N-PAHs on seedling emergence (over time) is in agreement with the findings of Hulzebos et al (1993), who reported higher toxicities of N compounds (pyridine, acrylamide and acetanilide) on plant germination and that of Gissel-Nielson and Nielson (1996), who reported that at 100 ppm navew seeds either did not germinate or if they did, the seedlings did not survive in acridine-amended soils. Similarly (although not in the soil environment), Pašková et al (2006) reported NPAHs as chemicals with the strongest inhibitory effects on germination and growth of plants using a liquid exposure media.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Several studies have reported that seed germination may be insensitive to toxic chemicals in soil as seedlings derive their food from internal materials (Sverdrup et al 2003;Eom et al 2007;Chung et al 2007;Smith et al 2006). In contrast, however, Henner et al (1999) reported that volatile, water soluble, low molecular weight hydrocarbons (<3-rings) such as 1,7-PHENANTHROLINE (wet biomass) TIME (d) In this current study, however, the observed inhibitory effect of N-PAHs on seedling emergence (over time) is in agreement with the findings of Hulzebos et al (1993), who reported higher toxicities of N compounds (pyridine, acrylamide and acetanilide) on plant germination and that of Gissel-Nielson and Nielson (1996), who reported that at 100 ppm navew seeds either did not germinate or if they did, the seedlings did not survive in acridine-amended soils. Similarly (although not in the soil environment), Pašková et al (2006) reported NPAHs as chemicals with the strongest inhibitory effects on germination and growth of plants using a liquid exposure media.…”
Section: Discussionsupporting
confidence: 86%
“…In support, Gissel-Nielson and Nielson (1996) reported that acridine inhibited the seed production of navew and growth of Italian rye grass. Similarly, Pašková et al (2006) recorded that only NPAHs (not the homocyclic PAHs) inhibited germination and growth of Sinapis alba, Triticum aestivum and Phaseolus vulgaris.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In particular the formation and distribution of polar PAC and their metabolites by intrinsic natural retention and degradation processes in the subsoil and aquifers of contaminated sites is the object of current research (13,(19)(20)(21)(22)(23). Our knowledge about formation, identification, distribution and degradation of these usually more polar, and in some cases toxic, compounds compared to their parent non-polar and poorly water-soluble PAH (24)(25)(26) is limited, nevertheless.…”
Section: Introductionmentioning
confidence: 99%